From 3 fingers to 5 fingers dexterous hands. (18th October 2017) - Ramírez Rebollo, Daniel R.; Ponce, Pedro; Molina, Arturo
Abstract: This document presents a resume of several robotic hands from 1983 to 2016, its aim is to cover this rapidly evolving field of robotics and provide relevant information about the designs and current developments. The characteristics of the hands are enlisted and compared in terms of weight, grasping power/load capacity, degrees of actuation, degrees of freedom and finger configuration. Some prosthetic hands are presented to show their similarities with the robotic ones. A clear design tendency is seen while the gap between merely robotic hands and prosthetic limbs closing. The final parts of this document expose the trends in design of robotic hands, human inspired or not. The design tends to be compliant providing high number of degrees of freedom achieving high dexterity but decreasing the number of actuators, these characteristics can provide robust performance. Finally, we suggest the standardisation on the development process of the robotic hands as most of them are meant to be used in household robots and human–robot interaction. Graphical Abstract: